2021
DOI: 10.3390/dairy2020021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Breed of Sheep on the Characteristics of Zamorano Cheese

Abstract: This work aimed to study the effects of using ewe’s milk from Churra, Assaf, or both breeds on the physicochemical and sensory characteristics of Zamorano cheese at the end of ripening. Zamorano cheese is a hard variety with protected designation of origin (PDO) produced in the province of Zamora (Spain) with raw or pasteurized ewe’s milk. Five batches of Zamorano cheese were produced with pasteurized ewe’s milk. One batch was elaborated using milk from the Churra breed, the other using milk from the Assaf bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Nevertheless, 4-methyl-C8, iC4 and iC6 were identified for the first time in Idiazabal cheese, as Amores et al [ 88 ] have reported for iC5, C7, C11, C13 and C15. There are differences in the lipolysis process during ripening or in the predominant FFAs compared to other raw ewe milk-derived cheeses [ 89 , 90 , 91 ]. For instance, Esmaeilzadeh et al [ 89 ] have reported a higher abundance of long-chain FFAs than short- or medium-chain FFAs during ripening of Kope cheese.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, 4-methyl-C8, iC4 and iC6 were identified for the first time in Idiazabal cheese, as Amores et al [ 88 ] have reported for iC5, C7, C11, C13 and C15. There are differences in the lipolysis process during ripening or in the predominant FFAs compared to other raw ewe milk-derived cheeses [ 89 , 90 , 91 ]. For instance, Esmaeilzadeh et al [ 89 ] have reported a higher abundance of long-chain FFAs than short- or medium-chain FFAs during ripening of Kope cheese.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of different types of cheese (Manchego, Roncal, Idiazábal, Cheddar, Dubliner, Zamorano) has been already studied by analytical techniques such as highperformance liquid (HPLC), gas (GC) or ionic chromatography, and by mass spectrometry [18][19][20]. Most of these analyses were focused on a determined group of compounds and required a sample pre-treatment, sometimes long and tedious extraction procedures, not avoiding the risk of sample alteration.…”
Section: Introductionmentioning
confidence: 99%